Modifiable sleep-related risk factors in infant deaths in Cook County, Illinois - Anna Briker; Suzanne McLone; Maryann Mason; Nana Matoba; Karen Sheehan (BMC, 2019)
Abstract Background Each year, approximately 3500 infants in the United States die from sleep-related deaths. The number of sleep-related infant deaths has decreased overall since the 1990s, but disparities in sleep-related deaths persist among different populations. The purpose of this study was to determine the most common risk factors and locations in Cook County, Illinois for sleep-related deaths in infants under 6 months of age. Methods We conducted a retrospective study among infants less than 6 months of age who died in Cook County, Illinois in 2015 and 2016, in which the manner of death was of undetermined intent with at least one modifiable sleeping risk factor present, as reported by the medical examiner. Data were obtained from the Illinois Violent Death Reporting System (IVDRS), a state-based, anonymous, surveillance system. County trends and circumstances of the deaths were also evaluated. Frequencies, percentages, and Chi-square analysis were used to describe and characterize these deaths. Results In Cook County in 2015 and 2016, 116 infants less than 6 months of age died where the manner of death was classified as undetermined intent. The median age of death was 2 months. Of these deaths, 63 (54.3%) of the infants were boys. African-American and Hispanic infants comprised 71 (65.7%) and 23 (21.3%) of the deaths, respectively. In 84 (72.4%) of the cases, at least one known sleeping risk factor was present and 56 (66.7%) of the infants who died with a known sleeping risk factor were co-sleeping. Notably, 33 (29.7%) of the deaths in Cook County were clustered within six zip codes. Conclusions The majority of infants who died unexpectedly in Cook County in 2015 and 2016 did so in the presence of sleeping risk factors, with co-sleeping being the most common. African-American infants, infants under 2 months of age, and several geographical areas within Chicago appear to be at increased risk. Interventions to target these preventable causes in the populations at increased risk should be instituted to prevent future deaths.